2021
DOI: 10.1007/s00595-021-02229-1
|View full text |Cite
|
Sign up to set email alerts
|

Online teaching of basic surgical skills to medical students during the COVID-19 pandemic: a case–control study 

Abstract: Purpose Medical education has been disrupted by the COVID-19 pandemic in many countries, with face-to-face lectures replaced by pre-recorded videos. However, surgical skills training cannot be replaced easily by videos, as a high level of tutor-student interaction is required. Thus, we developed a new web-based surgical skill learning session (WSSL). This case-control study evaluates the surgical skills competency of medical students taught by the WSSL. Methods This case-control study compares WSSL with face-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 7 publications
3
65
0
Order By: Relevance
“…Remote learning may in fact offer an opportunity to address and reduce such risks through repeated (virtual) exposure to correct techniques. Indeed, one recent study demonstrated basic surgical skills performance (which putatively holds greater risk) could be taught to medical students online with comparable levels of competency to conventional face to face teaching ( 16 ).…”
Section: Training Delivery Methodsmentioning
confidence: 99%
“…Remote learning may in fact offer an opportunity to address and reduce such risks through repeated (virtual) exposure to correct techniques. Indeed, one recent study demonstrated basic surgical skills performance (which putatively holds greater risk) could be taught to medical students online with comparable levels of competency to conventional face to face teaching ( 16 ).…”
Section: Training Delivery Methodsmentioning
confidence: 99%
“…VCT may optimize resources and increase training accessibility while retaining the quality of FFT. VCT has the potential to improve the global availability and accessibility of basic surgical skills training; however, its efficacy has not yet been firmly established [8,9].…”
Section: Choice Of Comparatorsmentioning
confidence: 99%
“…Co et al [ 9 ] in a systematic review reported that distance learning pedagogy has the potential to improve learner motivation and performance. Also, inexpensive e-learning solutions can be used to train complex procedures in medical education, such as surgical skills [ 10 ]. Therefore, e-learning holds the potential to improve student learning outcomes and experiences, especially in LMICs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Makokha et al [ 15 ] attribute the low adoption of e-learning in Kenya to a lack of ICT infrastructure and insufficient skills among faculty members. Co et al [ 10 ] note that even low-cost e-learning solutions may not be viable for students and teachers in economically less-privileged areas. Therefore, educational institutions, faculty members and students may find it difficult to use e-learning systems in resource-constrained settings.…”
Section: Introductionmentioning
confidence: 99%